Petrogenesis and tectonic implications of Early Paleozoic granitoids in the Baoshan deposit, Guangxi, South China - Lyu, Puliang; Liu, Fang; Chen, Ling; Song, Zhiguang; Ma, Wenen; Hou, Yanlin (Frontiers in Earth Science, 2024)
The Early Paleozoic tectonic setting and geological processes of the South China Block (SCB) have long been a subject of debate. This study presented zircon U-Pb geochronology and Hf isotope, and whole-rock geochemical analyses for the Early Paleozoic granitoids in the Baoshan deposit of the Dayaoshan Uplift. LA-ICP-MS zircon U-Pb results suggest that the diorites, granite porphyries, granodiorites and its mafic microgranular enclaves (MMEs) in the Baoshan deposit formed at 449-430 Ma.Their formation ages are consistent with those of granite, MMEs and mafic rocks found in the Dayaoshan region. The granite porphyries, granodiorites, diorites and their MMEs in the Baoshan deposit have high Eu/Eu* ratios, low Zr+Nb+Y+Ce contents, 10000×Ga/ Al values, and A/CNK ratios (0.74-1.08), belonging to metaluminous to weakly peraluminous calc-alkaline I-type granitoids. Based on zircon Hf isotopic compositions (εHf(t) from -5.5 to +3.1), it is unlikely that these rocks were solely originated from a crustal source, and mantle-derived magma also played a significant role in the formation of these intrusive rocks.It is inferred that the granitoids in the Baoshan deposit were probably formed through the underplating of mantle-derived magmas during a transitional collision to extension tectonic setting, which led to the remelting of Mesoproterozoic crust.